Sosialisasi Penerapan Teknologi Monitoring Tanaman Hidroponik di PPMI Shohwatul Is'ad Kabupaten Pangkep - Tahir, Zulkifli; Ilham, Amil Ahmad; Niswar, Muhammad; Adnan, Adnan; Zainuddin, Zahir; Paundu, Ady Wahyudi; Wardi, Wardi; Aswad, Iqra; Imran Oemar, Muhammad Alief Fahdal; Marindah Wardhani, Tyanita Puti (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Hydroponic plant cultivation refers to a method of cultivating plants that eliminates the use of soil as a growth medium. The present system possesses several notable benefits, including its ability to operate within a limited land area and the superior performance of hydroponic cultivation compared to conventional growing methods. This approach aligns with the concepts of the Sustainable Development Goals (SDGs), particularly SDG 2, which aims to ensure global food security. This public service aims to provide an Internet of Things (IoT)-enabled hydroponic production system that utilizes computer vision technology to regulate the provision of nutrients to plants based on their development rate. This technique is applicable to those in the general population who possess restricted land resources. Further, we aim to engage in community socialization around the hydroponic system while also offering insights into the newest advancements in information system technology applicable to hydroponics. We facilitate the acquisition of knowledge and skills within the community as a whole, with a specific focus on the students at PPMI Shohwatul Is'ad to equip them with the necessary expertise to effectively implement hydroponic plants and the latest information system technology for the purpose of monitoring.